Modified minimally invasive laparoscopic peritoneal dialysis catheter insertion with internal fixation - Xingzhe Gao; Zhiguo Peng; Engang Li; Jun Tian (Renal Failure, 2023)
Background Laparoscopic technique is widely used in peritoneal dialysis (PD) catheter placement. We developed a modified minimally invasive laparoscopic PD catheter (PDC) insertion with internal fixation and evaluated the early results by observing the intraoperative and postoperative conditions of the novel technique with those of conventional open surgery.Methods Retrospective research was performed on 59 patients who underwent PDC insertion from June 2019 to January 2022, including 23 patients who received open surgery and 36 patients who received modified minimally invasive laparoscopic surgery. Information such as preoperative conditions, operation time, incision length, incidence of intraoperative complications, time from operation to starting PD, time from operation to discharge, and incidence of catheter-related complications were collected and analyzed.Results The incision length, intraoperative blood loss, catheter migration rates and the total incidence of complications 6 months after operation in the laparoscopic group were lower than those in the conventional group. There were no statistically significant differences between the two groups in operation time, time from operation to starting PD, time from operation to discharge and the incidence of catheter blockage, leakage, exit-site infection, peritoneal dialysis associated peritonitis and hernia.Conclusions Modified minimally invasive laparoscopic PDC insertion and internal fixation method achieved direct vision and reliable fixation of the catheter, significantly reduced incision length and blood loss. The incidence of catheter migration was significantly lower than that of open surgery. Our primary findings reveal that modified minimally invasive laparoscopic PDC insertion with internal fixation is safe, effective and beneficial for PD patients.